The Analysis of Figure of Speech in Emily Dickinson's "Success Is Counted Sweetest" "I Had No Time To Hate", and "Have You Got A Brook In Your Little Heart" - Octavia Kurniawati; Masulah - (Tell : Teaching of English Language and Literature Journal, 2016)
The analysis provides the study about figure of speech, possible meaning and the total meaning in three poem’s of Emily Dickinson “success is counted sweetest”, “ I had no time to hate”, Have you got a Brook in your little heart”, This study tries to analyze figure of speech, possible meaning and the total meaning in statement of the problem. This analysis aims to analyze the types of figure of speech and possible meaning and to tell the total meaning of the Emily Dickinson poem’s. This analysis explains the design of qualitative method because it is related to the object of research. Qualitative description defines as research designed to produce a low inference description of a phenomenon that draws from discourse. The result of the research of the first poem “success is counted sweetest” figure of speech are Metaphor, Hyperbole, symbol, the second “ I had no time to hate” , the figure of speech is personification, Symbol. The last poem “Have you got a Brook in your little heart” figure of speech is personification, allegory.